PENGGUNAAN APLIKASI COOMIS (COMIC ISLAMI) SEBAGAI MEDIA DAKWAH UNTUK MEMUPUK SIKAP SEDERHANA PADA SISWA SD - FADILLA, DELIA DISA; Az-Zahra, Nalar; Nursaadah, Siti; Aeni, Ani Nur (Prodi PGMI STIT Sunan Giri Bima, 2023)
This research is based on the urgency of learning media in the Islamic Religious Education (PAI) learning process, which is also related to instilling simple attitudes in elementary school students. One way to cultivate simple attitudes in students is through the use of learning media in the form of the COOMIS (Islamic Comics) application. COOMIS is designed based on daily life experiences and perceptions of students. It presents three episodes of stories about simple living behavior in daily life, accompanied by animated characters, learning materials, and engaging quiz games. The method used in this research is the Design and Development (D&D) method involving 26 fifth-grade elementary school students and an Islamic Religious Education teacher. The results showed the feasibility and satisfaction of students in using the COOMIS application in the learning process, which was evidenced by the increase in pre-test and post-test results from 82.88 to 90.76 after using the COOMIS learning media, and a teacher questionnaire indicating the feasibility of the material and product aspects by 80%. Based on these results, it can be concluded that the use of learning media based on the COOMIS application developed by the researcher is very effective in the PAI learning process and is also feasible and effective for instilling simple attitudes in elementary school students.